Analysis of vegetation response to naturally occurring gaps in old-growth forests of Quercus ilex L. in Corsica - Panaiotis, C; Loisel, R; Roux, M (CANADIAN JOURNAL OF FOREST RESEARCH-REVUE CANADIENNE DE RECHERCHE FORESTIERE, 1998)
Green oak (Quercus ilex L.) is the most common forest species growing under Mediterranean climate. Because of important past anthropic perturbations, green oak old-growth forests are very unfrequent and constitute, for that reason, a most interesting domain where to analyze the natural evolution of green oak stands. Such forests exist in Corsica and this study deals with vegetation successions as they occur in naturally occuring gaps. Because of the taxonomic poorness (32 species), two statistical tools (canonical correspondence analysis and random permutations) were used to take into account vegetation spatial structure according to types (herbaceous, shrubby, or arborescent). These statistical analyses show that plant succession does not really exist in gaps of green oak old-growth forests but rather a structural organization of common species found in the maquis. Results support the hypothesis about the internal dynamics of these forests going through a maquis phase.
Keywords: natural gaps; quercus ilex forest; spatial structure; vegetation succession

Search for factors maintaining terricolous bryoflora richness in isolated habitats .2. Comparison between the sclerophyllous oak groves of the occidental border of the Massif des Maures (Var, France) and their interfaces with the vineyard (in French). - Hebrard, J P; Loisel, R (CRYPTOGAMIE BRYOLOGIE LICHENOLOGIE, 1997)
Processing (FAC) of 74 bryophytoecological releves from 6 forest structures with Quercus ilex or Quercus suber, isolated within the vineyard near Pierrefeu-du-Var (siliceous substratum), and the outlying contact zones : Prunus spinosa - Rubus or Cistus scrubs (I), bare soils or lawns often rich in ruderal species (i). The confrontation of the bryofloristical and the station data shows that ambient humidity and substratum richness in total nitrogen play an important role in the differenciation of terricolous bryophyte communities. Two forest sets, one humid and rich in nitrogen of organic origin (ubac of Defens du Becasson : surface = 77617 m(2), scrub-layer dense), the other dry and poor in that element (isolates and hedges with a surface less than or equal to 13115 m(2), scrub-layer absent) have been defined whereas a third, very xeric set, groups nearly all releves from the contact zone i, where supply in nitrate fertilizer may be important.
APS
Keywords: bryophyts; forests structure; Quercus ilex; Quercus suber

Dating natural gaps in the holm oak forest (Quercus ilex L) in Fango MAB Reserve (Corsica) by reading rings of maquis components - Panaiotis, C; Loisel, R; Paradis, G (Ann. For. Sci., 1995)
This work is related to the study of natural gaps in a Quercus ilex Mediterranean forest in Corsica, France. The aim was to find a way to precisely date the volis to obtain a chronological sample which corresponded to the time of vegetation opening due to the fall of a holm oak and up to complete vegetation closure. The best marker appeared to be Phillyrea latifolia, a typical maquis tree found in association with the holm oak, which has a high capacity to produce stem sprouts after the breakage. In order to date the chablis, rings from the stem sprouts must be counted and a careful observation of the other species must be made to confirm results.
Keywords: Corsica; Dendrochronology; Maquis; natural gap; Quercus ilex

SEARCH FOR FACTORS MAINTAINING TERRICOLOUS BRYOFLORA RICHNESS IN ISOLATED HABITATS - THE CASE OF SCLEROPHYLLOUS OAK GROVES OF THE OCCIDENTAL BORDER OF THE MAURES MASSIF (VAR, FRANCE) - Hebrard, J P; Loisel, R (CRYPTOGAMIE BRYOLOGIE LICHENOLOGIE, 1994)
Processing (FAC) of 25 bryophytoecological releves and quantitative analysis of bryofloristical inventories from 4 forest structures (surface values respectively 3976, 6160, 13115 and 77617 m2) isolated within the vineyard near Pierrefeu-du-Var (siliceous substratum) show that, for what concerns sclerophyllous oaks ecosystems (Quercus ilex, more rarely Quercus suber), the more humid the local microclimate is, the greatest are richness and diversity of terricolous communities of bryophytes. The optimal conditions for preservation of richness in forest bryophytes are here realized at the Defens du Becasson (surface: 77617 m2, maximum width: 151 m), a north-facing side which is well protected against the drying action of dominant winds and where the architecture of the ligneous formations is heterogeneous. On the other hand, the diversity of available microhabitants in the 2 largest isolates (strong slope, presence of clearings and disturbed skirts) contributes to increase their global richness in bryophytes. Furthermore, the presence of a dense layer of shrubs limits the accumulation of dead leaves on soil surface, allowing a good spread of the bryophyte layer and correlatively an enrichment in forest taxa when ambient humidity is high enough.
APS
Keywords: bryophytes; Microhabitats; Quercus ilex; Quercus suber

Changes and disturbances of forest ecosystems caused by human activities in the western part of the Mediterranean basin - Barbero, M; Bonin, G; Loisel, R; Quezel, P (Plant Ecology, 1990)
The development of socio-economic activity over the past ten years in the Mediterranean region has induced severe changes in the main natural forest ecosystems. In the northern Mediterranean, rural depopulation has accelerated since the end of the second World War, particularly since the establishment of Common Market agricultural policies, and led to an under-utilization of species causing a strong biological resurgence of the forest, even at high altitudes. This means that, at the present time, the extension of expansion model coniferous forests is favored by their capacities for spatial, biological and ecological selection. Along with this, the under-utilization of sclero- phyllous (resistance model) and deciduous (stabilization model) oak coppices has led to the establishment of new forest structures and architectures which are notably different from the main climatic groups defined up to now by phytosociological and synchronic methods. Two new forms of disturbances have appeared: - increasingly important wild fires have replaced disturbances caused by burn beating and are at the origin of the very strong spatial and temporal heterogeneity of current forest species. - In addition, the geographical continuity of the main groups of same-aged sclerophyllous and deciduous species, due to their non-use over the past ten years, has accelerated a phytosanitary imbalance by an increase in the action of pests. In the southern Mediterranean, particularly in North Africa, demographic pressure and grazing have widely disturbed the main forest ecosystems which show a continual regression of their surface. Many forest tree species with a low spatial and biological selection, such as Mediterranean firs and black pines (Pinus nigra subsp, mauritanica), are threatened with extinction, as are the deciduous oak forests which, considering the climatic stress and edaphic constraints, are permanently in a state of imbalance. Human disturbances induce a complete modification of structures and architectures tending towards the instal- lation of simplified forest models (trees-grasses) where tree regeneration is nearly impossible. The sclero- phyllous coppices well-adapted to stress are also threatened by shorter and shorter cutting cycles and by the high usage of tree canopies for grazing. - The forest understory structures have witnessed a decrease in their characteristic sylvatic species and the matorralization of most of the forests can be seen by the replacement of typical forest groups by preforest groups (Tetraclinis forests, Aleppo pine forests). - New geopedological constraints linked to the removal of the surface soil layer combined with regular climatic stress (duration of drought periods) strongly decrease the resilience of these ecosystems which are under continual pressure (unbalanced models). - In diverse regions, particulary in semi-arid bioclimates, hyperdegradation affects the shrub cover which disappears for a time in favor of perennial grasses (forest steppization): Andropogon div. sp., Ampelodesmos, Stipa div. sp. In all bioclimatic groups, the increase in grazing pressure throughout the southern Mediterranean ecosystems can even lead to the total disappearance of perennial species from the ecosystem with the exception of the dominant tree. Regardless of the altitude or ecosystem, invasive therophytes are then the only plants to occupy the understory and indicate hyperdegradation (forest therophytization).
Keywords: changes; disturbances; dynamic models; human activities; Mediterranean forests